Some Species of Adiantum from the Shivapuri National Park, Central Nepal - Singh, Sabina; Siwakoti, Mohan (Journal of Natural History Museum, 2015)
Four species of ferns belonging to genus Adiantum and family Adiantaceae were collected from Shivapuri National Park (ShNP). These were Adiantum capillus-veneris L., Adiantum caudatum L., Adiantum philippense L., and Adiantum raddianum C. Presl. Among these, Adiantum raddianum is reported for the first time from Central Nepal. J. Nat. Hist. Mus. Vol. 26, 2012: 198-202